Effects of Cooking and Chill-Reheating On Lipid and Flavor Characteristics Of S. Commerson and S. Guttatus - Rahimabadi, Eshagh Zakipoor (2008)

(untitled)
The cook-chill-reheating of foods are becoming more important in the catering industry today. However, reports on the potential changes on the nutrients such as lipid characteristics are negligible. Therefore, the objectives of the study were to determine the effect of cook-chill-reheating on the lipid characteristics, fatty acid composition and also flavor characteristics of the fish fillets. The lipid content, chemical characteristics i.e. free fatty acid (FFA), peroxide value (PV), iodine value (IV) and Thiobarbituric acid value (TBA), fatty acid composition, flavor profile, phospholipids and triglycerides content were determined in the raw and cooked and chilled-reheated samples. The sequential effect of cook-chill-reheating on the lipid and flavor characteristics in ‘Tenggiri batang’ (Scomberomorous commerson Lacepede, 1800) and ‘Tenggiri papan’ (S. guttatus Bloch and Schneider, 1801) fillets were studied. Cooked samples (by microwave, grilling, steaming and shallow fat frying) were chilled (4 ± 2 ºC) and then reheated using a microwave oven after 2 days. A two months frozen (-18 ºC) storage of raw material was studied to evaluate the effects of frozen storage on lipid characteristics prior to cooking. One and two way analysis of variance test (ANOVA) were used to analyze the effect of cooking by the afore mentioned methods and the two way ANOVA was used to analyze the effect of chill-reheating on the cooked samples. Principle components analysis (PCA) was used for visualizing and reducing the data. The lipid characteristics did not change significantly during the first two weeks of frozen storage. Cooking and reheating by the different methods significantly (P<0.05) changed the FFA, PV and TBA content in both fish. The initial lipid content of S. commerson (2.3%), significantly changed to 4.0, 2.6, 3.6 and 4.8 % after microwave cooking, grilling, steaming and shallow fat frying; and for S. guttatus the initial lipid content of 6.0% changed to 7.0, 10.5, 5.4 and 10.3 %, respectively. Significant increase in lipid content were observed in steamed samples after reheating in both fish, and in grilled and fried samples of S. commerson. Both cooking and chilling-reheating affected (P<0.05) the fatty acid composition. Higher concentrations of C16:0, C18:1 n-9 c and C18:2 n-6 c were observed in shallow fat fried samples. Frying significantly increased the amount of n-6 FAs in both fish. Reheating caused a slight increase in the amount of SFA / PUFA and also the n-6/ n-3 ratio in all cooked samples. The C22:6/C16:0 ratio decreased in all cooked and reheated samples. Alkanes-alkenes were the major group of volatile compounds of raw samples in both fish. Cooking generated new compounds and increased the concentration of volatile component from 72.8 to 111.1, 74.3, 112.2 and 92.4 μg/kg for S. commerson and from 63.6 to 67.4, 77.80, 65.8 and 67.1 μg/kg for S. guttatus after microwave cooking, grilling, steaming and frying, respectively. Reheating also caused changes in the number and the concentration of the volatile compounds. In S. commerson, only shallow fat frying significantly increased the TG content. In S. guttatus there were no significant changes in the triglycerides and phospholipids content in the cooked samples. Slight increase in the amount of TG content was detected in all cooked samples of S. commerson during chill-reheating. The TG content of microwave cooked and steamed samples of S. guttatus, slightly decreased after chill-reheating.